Efecto de teflubenzuron a diferentes concentraciones en el control de nematodos en el cultivo de banano musa aaa - Chuya Zhangallimbay, Jose Oswaldo (2017)
The cultivation of banana (Musa sp) is one of the main types of agricultural production of the province of El Oro and of Ecuador, making is one of the principal sources of employment and of great economic movement in the area, to turn this spice has been affected by its morphology that to be herbaceous makes it very susceptible to pests and diseases such as nematodes that have been constituted in one of the pathogens that directly affect the production in the cultivation of bananas because they live mainly in the soil and the roots and that in the case of bananas these species are more harmful because they spend the greater part of their life cycle in The tissues of the root and corm , whose attack occurs when hosting their roots feeding it causing low performance and affecting the quality of the bunch leading to the toppling of plants to be destroyed its root system, for its control have established different mechanisms to reduce their population in the soil which have been products chemically synthesized to affect their physiology and consolidate its eradication of the root system. Recent studies in the control of nematodes have put the teflubenzorun as an alternative in the management of these fitoparásitos in which their background are studied in this investigation despite that is applied to control insects, whose purpose of this work is to evaluate the effect of teflubenzorun at different concentrations for the control of nematodes in the cultivation of bananas by determining the percentage of roots and the number of nematodes present in the roots evaluated, for they established a randomized block design with five treatments (T1:0.4%,T2:0.8%,T3:1%,T4:1.5%,T5: witness) established in banana plots and in a greenhouse in which for the phase of field is prepared substrate using earth, sand, rice husks, formol whose Substrate must be clean and free of any health problem. Once disinfected the substrate is proceeded to fill the experimental units where they were going to be sown plants of banana, Once planted the plants are left to acclimatise for about 5 days in the greenhouse to then inoculate nematodes on each floor (90ml = 1080 nematodes/plant) shortly after the inoculation nematodes are fixed by other 8 days more and then apply the dose of each treatment. Done all this methodology was used for the study of each variable to the 20, 40 ,60 days in the laboratory of the Academic Unit of Sciences Agriculture of the Technical University of Machala whose results of the treatments were significant on the witness to the 20 days of applying, while in the 40 and 60 days, there was no such significant effects due to the authors express that the teflubenzorun tends to lixiviarse quickly from the 29 days of application to be degraded by microorganisms and depending on the type of soil as in the sandy soil that is lost quickly or in cases of exist high organic matter in the soil the colloid what Retains in its particles causing that has a more lasting effect in the soil, concluding that the effect of the teflubenzorun has insignificant effect on the nematodes and that is not very detrimental to the microfauna of the ground.